Time-dependent effects of unfractionated heparin in patients with ST-elevation myocardial infarction transferred for primary angioplasty. (1st November 2015) - Giralt, Teresa; Carrillo, Xavier; Rodriguez-Leor, Oriol; Fernandez-Nofrerias, Eduard; Rueda, Ferran; Serra-Flores, Jordi; Viguer, Josep Maria; Mauri, Josepa; Curos, Antoni; Bayes-Genis, Antoni
Abstract: Aims: Initial thrombolysis in myocardial infarction (TIMI) flow and mortality are related in ST-elevation myocardial infarction (STEMI) patients treated with primary angioplasty (PPCI). It is unclear whether early adjunctive treatment with unfractionated heparin (UFH) is beneficial for coronary patency. We investigated the effect of UFH administered before transfer versus in the catheterization laboratory (CathLab) on initial patency of the infarct related artery (IRA) in transferred STEMI patients treated with PPCI. Methods and results: Consecutive STEMI patients (n = 1326, February 2007–December 2013) were allocated in two groups relative to UFH administration: pre-transfer group — administration by ambulance crew or physician-in-charge at the non-PPCI centre, 758 patients (57%); post-transfer group — administration in the CathLab, 568 patients (43%). The time range between symptom onset (SO) and UFH administration (SO–UFH) was assessed and the 1-year mortality prediction was analysed by logistic regression. Initial IRA TIMI 2-3 flow was 30.3% in pre-transfer group vs. 21.2% in post-transfer group (p < 0.001). A time-dependent association was found between SO–UFH and initial TIMI 2-3 in pre- vs. post-transfer groups [< 120 min: 33.2% vs. 18%, p < 0.001; 120–240 min: 29.2% vs. 22.8%, p = 0.18; > 240 min: 25% vs. 28%, p = 0.57]. No differences in major bleeding were found between groups. UFH administration before transfer remained an independent predictor for initial TIMI 2-3 flow (OR 1.60 CI 95% 1.22–2.11, p = 0.01) and for 1-year mortality (OR 0.51 CI 95% 0.29–0.91, p = 0.02). Conclusions: Early UFH administration in STEMI patients transferred for PPCI results in higher IRA initial patency in a time-dependent manner and improves clinical outcomes.